2006
DOI: 10.1152/jn.00623.2006
|View full text |Cite
|
Sign up to set email alerts
|

Intracortical Circuits in Rat Anterior Cingulate Cortex Are Activated by Nociceptive Inputs Mediated by Medial Thalamus

Abstract: We investigated the afferents and intracortical synaptic organization of the anterior cingulate cortex (ACC) during noxious electrical stimulation. Extracellular field potentials were recorded simultaneously from 16 electrodes spanning all layers of the ACC in male Sprague-Dawley rats anesthetized by halothane inhalation. Laminar-specific transmembrane currents were calculated with the current source density analysis method. Two major groups of evoked sink currents were identified: an early group (latency = 54… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
57
0

Year Published

2008
2008
2020
2020

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 65 publications
(62 citation statements)
references
References 85 publications
5
57
0
Order By: Relevance
“…30 There are many studies on the implication of Glu in nociception. [31][32][33] In particular, an increase of Glu at the level of anterior cingulate cortex was demonstrated by Mullins et al 34 in association with painful stimuli, and these variations correlated with the perceived pain intensity. Our results confirm this glutamatergic alteration, and the increase of Glx/Cr and Glu/Cr in both VLPFCs and not in thalami adds new insight into the physiopathology.…”
Section: Discussionmentioning
confidence: 93%
“…30 There are many studies on the implication of Glu in nociception. [31][32][33] In particular, an increase of Glu at the level of anterior cingulate cortex was demonstrated by Mullins et al 34 in association with painful stimuli, and these variations correlated with the perceived pain intensity. Our results confirm this glutamatergic alteration, and the increase of Glx/Cr and Glu/Cr in both VLPFCs and not in thalami adds new insight into the physiopathology.…”
Section: Discussionmentioning
confidence: 93%
“…Intraperitoneal and intracortical injections of morphine enhanced the sink currents in the ACC evoked by noxious electrical stimuli [24] . However, studies in patients with predominantly post-stroke pain demonstrated that there is significantly less opioid receptor binding in ACC [36,37] .…”
Section: Neurotransmitter and Receptor Mechanisms Underlying Acc Invomentioning
confidence: 97%
“…The mRNA expression level of metabotropic glutamate receptor 3 (mGluR3) is significantly increased in cortical areas of monoarthritic rats, including the contralateral cingulate cortex [32] . Intracortical injection of glutaminergic receptor antagonist inhibited the sink currents in the ACC evoked by noxious electrical stimuli [24] . Consistent with this finding, chemical activation of the NMDA receptor or mGluR in the ACC decreased the latency of the paw-withdrawal and tail-flick responses to heat stimulation [26,27] .…”
Section: Neurotransmitter and Receptor Mechanisms Underlying Acc Invomentioning
confidence: 98%
See 1 more Smart Citation
“…An ACC nociceptive signal arises in the parafascicular thalamic nucleus (Pf) as shown with lidocaine block (Sikes and Vogt, 1992) and ACC is driven by MITN according to lesion (Yang et al, 2006), electrical V. CORTEX stimulation of the thalamus (Hsu and Shyu, 1997;Hsu et al, 2000), and a high correlation between MITN and ACC nociceptive responses (Lee et al, 2007). Nociceptive responses are not limited to ACC as neurons in M2 are driven by noxious cutaneous and colonic stimuli (Sikes and Vogt, 1992;Shih et al, 2008;Wang et al, 2008).…”
Section: Nociceptive Thalamic Afferentsmentioning
confidence: 99%